PENGARUH PUASA INTERMITEN TERHADAP NILAI TRIGLISERIDA PASIEN OBESITAS DI SURABAYA - Renata Primasari; Deorina Roully Gratia Siregar (Jurnal Medicare, 2026)
Background: Obesity is frequently accompanied by hypertriglyceridemia, which increases cardiometabolic risk. Objective: To evaluate the effect of a 12-hour intermittent fasting regimen, performed on three non-consecutive days per week for six weeks, on triglyceride levels in patients with obesity. Methods: This quasi-experimental study employed a non-equivalent control group pretest–posttest design involving 50 participants, divided into an intervention group (n=25) and a control group (n=25). The intervention group fasted from 06:00 to 18:00, while the control group maintained their usual dietary habits. Fasting triglyceride levels were measured before and after the intervention. Data were analyzed using paired tests, Welch’s t-test, and ANCOVA. Results: Triglyceride levels decreased from 251.64 to 178.80 mg/dL in the intervention group and to 227.20 mg/dL in the control group. The adjusted reduction was significantly greater in the intervention group by 48.40 mg/dL (95% CI: 33.60–63.20; p<0.001), with a compliance rate of 90.2%. Conclusion: A 12-hour intermittent fasting regimen performed three times weekly for six weeks reduced triglyceride levels more effectively than a usual diet. Larger randomized controlled trials are needed to confirm these findings. Intermittent fasting may represent a simple, low-cost intervention with potential application in primary healthcare, accompanied by continuous monitoring of dietary intake and physical activity.